Study On the Urgency of Women's Legislative Representations Local Parties, Langsa City, Aceh Province - Alfian Lukman; Taufik Abdullah; Taufik Saputra; Herdi Sahrasad (Budapest International Research and Critics University, 2022)
This study examines the phenomenon of the lack of women's representation, the challenge of affirmation of 30 percent, the urgency of female legislators, framing the actual context and discourse on strengthening gender-sensitive female legislators. Through a qualitative approach, a number of phenomena were explored in descriptive analytical manner. The findings of the study explain the lack of representation because patriarchal culture still shackles internal political parties. Women are only used as a complement to the requirements to participate in elections. Weak access and freedom during the campaign season as well as the flexibility of the voter network are among the factors that make it difficult to fulfill the representation of women legislators. As for their choice, they are fully supported by social networks, kinship relations and family solidity. The role of legislators is limited to carrying out formal and responsive obligations according to constituent requests or needs. The articulation that is highlighted is a variety of religious social actions. The conclusion of this study confirms that female legislators have not substantively influenced gender-based policies. The commitment of political parties to fulfill women's representation by carrying out potential candidates elected based on a social network and family kinship approach deserves further investigation. This strategy is not impossible for the representation of 30 percent of women legislators to be fulfilled in the future.